OPTIMIZATION OF BUDGET EXPENDITURES FOR THE DEVELOPMENT OF ENTERPRISES (OPK) - A. Z. Namitulina (Модернизация, инновация, развитие, 2015)
Optimization of state budget expenditures towards the development of military-industrial complex is one of the priorities of the current economic reforms. In addition, there are several features of allocation of fi nancial support in the military-industrial complex, which are due to problems of national security. Production of defense enterprises should be implemented, especially in the framework of a single defense order, which is not always benefi cial to the manufacturer, this requires a well-organized process of redistribution of the state budget.